A COMPARATIVE STUDY OF QUALITY CONTROL TESTING OF MEFENAMIC ACID TABLETS IN IRAQ - ABDULRAZZAQ, INAS F.; SALAL, YASMIEN A.; ABDUL-HASAN, MAZIN THAMIR; ABBAS, HAYDER K.; HASAN AL-GBURI, KARRAR MOHAMMED (International Journal of Applied Pharmaceutics, 2022)
Objective: This research was performed to assess the quality of different marketed tablets having mefenamic acid (500 mg). The selected tablets are produced by numerous companies and presented in the Iraqi pharmaceutical marketplace. Methods: Different batches of mefenamic acid conventional tablets were exposed for several tests of quality control. These evaluation tests include hardness, weight variation, friability, disintegration time, drug content, and drug dissolution profile. The properties of these quality tests were made conferring to the specification of USP-pharmacopeia. Results: The data of this study indicate that each tablet of mefenamic acid batches conformed to the requirement of USP pharmacopeia, the hardness was (6.87-8.06 Kg/cm2), and the drug content results were (90.666-99.214%) within USP limitation. The data of disintegration time and weight uniformity were agreeable with pharmacopeia and the in vitro release assay showed that the release of each mefenamic acid marketed tablet was highest than (80 %) in 45 min, which reproducing compliance with the USP pharmacopeia's limitation. Conclusion: From this study, it was proved that all of the marketed brands of mefenamic acid tablets meet the standard character in the USP pharmacopeia for in vitro quality control tests.